Antagonism in Orthotospoviruses Is Reflected in Plant Small RNA Profile - Md Tariqul Islam; Kaixi Zhao; Nathan Johnson; Michael Axtell; Cristina Rosa (Viruses, 2025)
Mixed infections of plant viruses are commonly found in natural patho-systems and present a valuable opportunity to understand how multiple viruses can co-infect the same host. Tomato spotted wilt orthotospovirus (TSWV) and impatiens necrotic spot orthotospovirus (INSV) are present in the same geographic areas and are closely related. More mixed infections of TSWV and INSV have been reported in recent years, and the INSV host range has been reported to be increasing. In a previous study, we isolated and characterized one strain of INSV and one of TSWV and found that they have an antagonistic relationship in their vectors. However, we were unable to determine whether this antagonism extends to the host plant or to uncover the underlying mechanisms and the host’s contribution. Here, we show that TSWV and INSV exhibit antagonistic interactions in the host plant, as evidenced by a lower viral titer in mixed infections compared to single infections. Using small RNA sequencing, we identified that the host plant contributes to this antagonism through differential small RNA processing, which appears to regulate viral replication and the success of infection. This research advances our understanding of virus–virus and virus-host interactions and presents opportunities for leveraging these dynamics in integrated pest management strategies.